2015
DOI: 10.1371/journal.pone.0137580
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Critical Congenital Heart Disease: Newborn Screening Using Pulse Oximetry for Neonatal Sepsis and Respiratory Diseases in a Middle-Income Country

Abstract: BackgroundStudies on pulse oximetry screening for neonatal sepsis and respiratory disease in a middle-income country are lacking. Newborn screening for critical congenital heart disease (CCHD) using pulse oximetry is an effective and life-saving strategy in developed countries. While most studies have reported false-positive results during CCHD screening, they have not elaborated on the detected disease types. We studied the effectiveness and outcomes of pulse oximetry newborn screening for non-cardiac hypoxem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Reports outside of the United States show similar performance of pulse oximetry screening in identifying critical congenital HD, 95 with a sensitivity and specificity of pulse oximetry screening for critical congenital heart defects of 100% and 99.7%, respectively.…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 80%
“…Reports outside of the United States show similar performance of pulse oximetry screening in identifying critical congenital HD, 95 with a sensitivity and specificity of pulse oximetry screening for critical congenital heart defects of 100% and 99.7%, respectively.…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 80%
“…Failure to reach a centre capable of performing this intervention may result in death. 2 The value of pulse oximetry screening for the detection of other hypoxaemic conditions such as respiratory or infectious diseases has been recognised 28,29 and may be of particular importance in settings where the majority of those with cardiac disease are diagnosed in the antenatal period. In view of this, we designed an intervention study to explore the impact of pulse oximetry screening in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies demonstrated that use of SPO2 for screening for CCHD at discharge was effective, feasible, and had comparable cost with the existing newborn screening tests. It has also been reported that it can easily be integrated with the existing referral system if community-based screening has to be implemented,1416 with negligible increment of service burden to the hospital because of implementation 23. However, in our study no case of CCHD was detected by using the SPO2 screening test.…”
Section: Discussionmentioning
confidence: 51%